Significance of ocular stem cells in tissue engineering of the eye (Medical Journal of Indonesia, 2008)
Blindness is one of the most devastating condition for mankind. Regenerative medicine through tissue engineering and optimizing tissue regeneration through local adult stem cell differentiation or stem cell transplantation has received a lot of attention. This review presents highlights in the discovery of ocular stem cell and in vivo experiment for stem cell transplantation and current trends in tissue engineering of the eye. (Med J Indones 2008; 17: 143-8)